The Extra-Phenomenal - Falque, Emmanuel (Diakrisis, 2018)
Everything is phenomenon, everything is gift, or everything is given. This presupposition of phenomenology, which makes givenness (Gegebenheit) the starting point for phenomenality, is not altogether self-evident. It is not sufficient to look merely at the reverse of the gift (phenomenology of the night), but it is a matter of questioning the impossibility of even giving (the night of phenomenology). Questioning the strategies of the contemporary reappropriations of Kant—radicalization (Heidegger), disproportion (Ricœur), and inversion (Marion)—this text works under a fourth possibility, seldom examined and yet still envisaged by Kant: the "Extra-Phenomenal", or in other words, the "Chaos", the "pell-mell", the "Cinnabar", or the "melee of sensations".